2015
DOI: 10.2174/1874155x01509011067
|View full text |Cite
|
Sign up to set email alerts
|

Fault Diagnosis for Steam-flow Exciting Vibration of Ultra Supercritical 1000 MW Steam Turbine

Abstract: With the increase in thermal power capacity, ultra supercritical units have become the mainstream of power industry. At the same time, with the improvement of the steam parameters and the lengthening of shafting, the production of steam flow excited vibration is frequent in the ultra supercritical units, which may seriously affect the reliability of the unit. This paper has taken steam flow excited vibration of a 1000MW turbine as an example in accordance with the experimental and theoretical causes of steam f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In recent years, with the rapid development of fault monitoring and diagnosis technology, more and more comprehensive intelligent diagnostic technology can detect potential dangers before catastrophic equipment failures, improve equipment reliability and safety, at the same time, it can reduce the operation and maintenance cost of complex engineering system. Therefore, the health monitoring and fault diagnosis of gear machinery is of great significance [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of fault monitoring and diagnosis technology, more and more comprehensive intelligent diagnostic technology can detect potential dangers before catastrophic equipment failures, improve equipment reliability and safety, at the same time, it can reduce the operation and maintenance cost of complex engineering system. Therefore, the health monitoring and fault diagnosis of gear machinery is of great significance [11][12].…”
Section: Introductionmentioning
confidence: 99%
“…There are a variety of signals that can be used for health monitoring, such as vibration, sound, temperature, crack and pressure. In the actual monitoring, it can be found that the vibration signal is most widely used (Li, 2001). The vibration is common for the mechanical equipment, and the mechanical damage is often caused by vibration (Li, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As early as the 1980s, the United States discovered that as much as 150 million dollars were spent in power sector on repairing the erosion damaged turbine cascades. 4 Research by Liu 5 showed that the severe tearing of nozzle trailing edge by SPE would reduce the stage efficiency by 15–20%, resulting in significant economic losses. Therefore, how to effectively reduce or eliminate SPE of cascade has been a main issue concerned by power companies and experts.…”
Section: Introductionmentioning
confidence: 99%